ANDRELLO, Geraldo. 2006. Cidade do Índio. São Paulo: Editora UNESP/ISA; Rio de Janeiro: NUTI. 447 pp. - Nunes, Eduardo Soares (Campos - Revista de Antropologia, 2008)
Resenha do livro Cidade do Índio, de Geraldo Andrello, publicado em 2006.